PERANCANGAN APLIKASI PENGAMANAN DATA TEXT MENGGUNAKAN KOMBINASI ALGORITMA HILL CIPHER DAN ALGORITMA RSA - Prabowo, Dedy Agung; reswan, yuza (Major of Information Systems Faculty of Computer Science Sriwijaya University, 2018)
It is now commonplace that secrecy must be truly enhanced and tightened as it weighs the emergence of the latest technology that is growing rapidly. Of course an agency, group, or individual have data that is confidential and do not want to be known by other parties hence the need for a system capable of securing the data. For this reason this research aims to create Cryptography application by applying a combination of Hill Cipher and RSA algorithm, Cryptography is also called coding language and I apply Hill Cipher because it is a classical method that uses multiplication for each encoded character while RSA is a modern method that has 2 keys ie key public and secret key where the public key is used for encryption and secret key to retranslate the original form. By applying a combination of classical and modern methods it can be more secure so it is more difficult to be solved by unwanted parties. Keyword : Data Security, Cryptography, Hill Cipher, RSA